COMPARATIVE ANALYSIS OF THE PHYSICAL CULTURE AND SPORTS SPECIALISTS TRAINING FOR THE FUTURE PROFESSIONAL ACTIVITIES IN UKRAINE AND ABROAD - REBUKHA, Liliya; LIU , Han (ГУМАНІТАРНІ СТУДІЇ : ІСТОРІЯ ТА ПЕДАГОГІКА, 2023)
Annotation. In the article a comparative analysis of physical culture and sports specialists training for future professional activities in Ukraine and abroad is carried out. The relevance of the study is due to the fact that nowadays in every society there is a growing awareness of the importance of a healthy lifestyle and regular physical activity for the preservation of human health. Accordingly, the main roles of physical culture and sports in this process are emphasized as an effective mechanism of physical, moral, mental and spiritual development of the individual. One of the tasks of a modern institution of higher education is the training of specialists in physical culture and sports in the modern educational space of Ukraine and the disclosure of such training abroad. Solving these tasks contributes to the maintenance and promotion of a healthy lifestyle, the development of physical activity, and therefore the achievement of high results in professional activities. The research established that the domestic experience of training physical culture and sports specialists is characterized by the acquisition of knowledge and skills of the organization of health and recreational physical activity of various population groups, sports training and support of athletes in competitions. We consider the national training of future specialists in physical culture and sports as a complex, complicated and multifaceted process, which includes the formation of worldviews and value attitudes in this area, the creation of a motivational field in the process of education aimed at realizing the importance of this type of professional activity, their acquisition of theoretical knowledge and development necessary skills and abilities. The main components of university training are highlighted: theoretical foundations and practical skills, professional ethics and leadership, adaptability to changes, continuous learning and professional development. The essence of the psychological-pedagogical training of future physical culture and sports specialists with the formation of their readiness to implement "subject-subject" relationships in their future activities is indicated. A comparative analysis of physical culture and sports teachers training was conducted on the example of China, which takes place in accordance with the laws of their professional development, step by step and with strict adherence to systematicity. An important aspect of a specialist's training is familiarizing them with the theory and methodology of teaching, learning various types of sports and sports training technologies, and fostering self-development skills and self-education. Therefore, the training of future specialists in the field of physical culture and sports in Ukraine and abroad (on the example of China) include methodical and psychological readiness of the future specialists for future work and understanding the importance of this type of profession for civil society.